“Organizational Terrorism” and Moral Choices – Exercising Voice When the Leader is the Problem - Caldwell, Cam; Canuto-Carranco, Mayra (2010)
We introduce the concept of “organizational terrorism” to describe dysfunctional leaders who are abusive and who treat organizational members with contempt and disregard. After identifying the moral duties of leaders in organizations, we explain how organization members respond to their dissatisfaction with organizations through Exit, Voice, Loyalty, or Neglect. We explain why exercising voice is the most effective moral choice in dealing with dysfunctional leaders.
Keywords: organizational citizenship; Neglect; Loyalty; Voice; Exit; Ethical Leadership; organizational terrorism